2022
DOI: 10.1001/jamaophthalmol.2022.0858
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Altmetric Attention Scores and Citations for Articles Published in High–Impact Factor Ophthalmology Journals From 2018 to 2019

Abstract: attention score (AAS) provides new information to gauge the impact of a research article not found through typical metrics, such as impact factor or citation counts.OBJECTIVE To explore the association between AAS and common impact markers among high-impact ophthalmology journals from 2018 to 2019.DESIGN, SETTING, AND PARTICIPANTS All articles published in the American Journal of Ophthalmology (AJO), JAMA Ophthalmology (JAMAO), and Ophthalmology (OPH) from January 1, 2018, to December 31, 2019, were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…To the Editor In a recent issue of JAMA Ophthalmology, Djulbegovic et al 1 describe the correlation of Altmetric Attention Score (AAS) and citation number for articles published between 2018 and 2019 in 3 major ophthalmology journals, the American Journal of Ophthalmology, JAMA Ophthalmology, and Ophthalmology. 1 The AAS is a weighted average based on the number of social media website mentions. 2 One advantage of AAS is that it can be used to more immediately observe the perceived impact of recent articles, whereas it may take years for citation counts to grow to a meaningful level for comparative analysis.…”
Section: Altmetric Attention Scores In Ophthalmology Journalsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor In a recent issue of JAMA Ophthalmology, Djulbegovic et al 1 describe the correlation of Altmetric Attention Score (AAS) and citation number for articles published between 2018 and 2019 in 3 major ophthalmology journals, the American Journal of Ophthalmology, JAMA Ophthalmology, and Ophthalmology. 1 The AAS is a weighted average based on the number of social media website mentions. 2 One advantage of AAS is that it can be used to more immediately observe the perceived impact of recent articles, whereas it may take years for citation counts to grow to a meaningful level for comparative analysis.…”
Section: Altmetric Attention Scores In Ophthalmology Journalsmentioning
confidence: 99%
“…Breast carcinoma is a malignant condition of mammary epithelial cells that accounts for the greatest number of new cancer cases in female patients (30%) and the second most common number of cancer-related deaths in female patients (15%). 1 Shields et al 2 assessed 1111 consecutive patients with uveal metastasis and found breast cancer represented 37% of cases, with a mean age at presentation of 57 years and Kaplan-Meier 5-year survival of 24%. In that same cohort, Welch et al 3 noted a mean interval of 6.5 years between primary breast cancer diagnosis and uveal metastasis.…”
mentioning
confidence: 99%
“…AAS is a dynamic bibliometric which captures the online impact of a paper. It has been used to assess the online impact of journal articles across diferent felds [7,14,21] and provide potential evidence for research impact or journal strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In ophthalmology, studies have demonstrated a weak to moderate correlation between the AAS and conventional metrics such as the number of citations and H-index. (11)(12)(13) A recent study showed that publications that are promoted on Twitter end up having a higher number of citations than the ones with no tweets. (14) In a study looking into publications from a different specialty (cardiology), Twitter promotion was linked with a 1.12 higher citation rate.…”
mentioning
confidence: 99%